(untitled) (Itinera, 2022)
The idea that colour can have a psychological impact and in some way influence emotions has specific historical roots in the origins of modern visual culture. Therefore, this essay considers, in an epistemological perspective, the study of colour as a problem within the history of perception. Focusing on some key issues of the late 19th century artistic, cultural and psychophysiological debate on synaesthesia – in relation to the theories on colour and emotion –, this research interrogates in particular the link between image, sound, colour and the developments of chromatic music. The turn of the 20th century is a crucial moment to understand the historical basis of a new interpretation of colour, whose aesthetic effectiveness is connected to its power of conditioning the spectator’s senses. This article argues that the resulting emphasis on the viewer’s embodied reaction to colour also leads to rethink the status of still and moving images within the framework of immersive colour experiences based on the relationship between body, medium and senses.